2022
DOI: 10.1186/s12879-022-07893-3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of HPV infection in 40,693 women in Putian: a population study based on screening for high-risk HPV infection

Abstract: Background The infection rate of human papillomavirus (HPV) is high in the coastal regions of China. However, the infection rate among high-risk genotypes of women in Putian City is unknown. Therefore, this study aimed to analyse the epidemiology of high-risk HPV infection among women in Putian and provide a reference for the diagnosis, treatment and vaccination of cervical cancer in this region. Methods The data used were obtained from the Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…On the other hand, as the illness advanced, the proportions of HPV39, 51, and 52 steadily decreased. These results were consistent with previous findings [ 10 , 34 ]. In multiple infections, high-risk HPV was less likely to progress to HSIL than in single infections.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, as the illness advanced, the proportions of HPV39, 51, and 52 steadily decreased. These results were consistent with previous findings [ 10 , 34 ]. In multiple infections, high-risk HPV was less likely to progress to HSIL than in single infections.…”
Section: Discussionsupporting
confidence: 94%
“…At present, the significance of HR-HPV infection, especially HPV16/18 persistent infection, for cervical cancer has been recognized by most clinicians. Our study showed that the HPV infection rate was 20.27%, a decrease from 22.97% in the same region previously ( 9 ), which may be related to higher education, widespread HPV vaccination, or an increase in average socioeconomic level ( 10 , 11 ). HPV infection rate was higher in women aged <30 and ≥50 years; this was consistent with the previously reported double-peak distribution of HPV infection rates, which was considered to be related to the frequent sexual life, smoking, and oral hormonal contraceptive use in young women ( 11 , 12 ), as well as the changes in sexual behavior, low autoimmunity, and the reactivation of menopausal latent HPV in older women ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 48%
“…The general infection rates in this study were lower than those in previous surveys in Central Fujian (38.3%, χ2 = 2169.7, P < 0.0005) [ 11 ], Zhejiang (22.3%, χ2 = 600.96, P < 0.001) [ 10 ], and Shanghai (Putuo Hospital) (18.8%, χ2 = 76.9, P < 0.005) [ 12 ] but greater than that in Xi’an (13.5%, χ2 = 52.8, P < 0.01) [ 13 ] and Shandong (16.4%, χ2 = 1.2, P > 0.1) [ 14 ]. The percentage in the healthy group was greater than that in the Putian group (9.6%, χ2 = 92.52, P < 0.005) [ 15 ] and lower than that in the Zhejiang group (13.6%, χ2 = 15.8, P < 0.025) [ 10 ], Fujian group (a cross-sectional study) (16.2%, χ2 = 24.3, P < 0.025) [ 16 ], and Beijing group (11.9%, χ2 = 0.16, P > 0.1) [ 9 ]. The results for the patient group were not significantly different from those for Henan (19.7%, χ2 = 3.91, P > 0.05) [ 17 ] or Guangxi (18.1%, χ2 = 6.3, P > 0.05) [ 18 ] but were lower than those for Beijing (21.0%, χ2 = 20.4, P < 0.025) [ 19 ] and Zhejiang (27.3%, χ2 = 587.8, P < 0.001) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%